2021
DOI: 10.1051/e3sconf/202123203004
|View full text |Cite
|
Sign up to set email alerts
|

Input Saving Technology Package of True Seed of Shallot (TSS) Production in Indonesia

Abstract: True seed of shallot (TSS) can be an alternative source of shallot seeds. But the use of TSS in Indonesia is still limited because not many people produce TSS because of high input production. This research aimed to evaluate the technical and economic feasibility of input saving TSS production technology packages. The research was carried out in Ciwidey district, Bandung Regency, West Java, Indonesia from June to October 2016. The research consisted of two factors arranged in a split plot with a randomized blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In addition, the Bima variety has a wide adaptability. It is proven that this variety grows well in the lowlands to the highlands [22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Bima variety has a wide adaptability. It is proven that this variety grows well in the lowlands to the highlands [22][23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%
“…The germination rate, plant height, and number of leaf per plant of TSS seedlings were not affected by interaction between seedling media and sowing method + sowing depth [27]. The TSS germination rate for Bima variety was generally low on each treatment of seedling media and seed sowing method, averaging 36.67%-77.33% [32]. Research identifying Bima variety seed structure showed low seedling emergence because of its thick seed skin (testa), which hinders water absorption.…”
Section: B Agronomic Performancesmentioning
confidence: 99%
“…The IVEGRI technology package was able to increase the garlic bulb diameter to 32.69 % and bulb weight to 11.5 g [11]. However, the application of introduced technology could increase the cost of farming and burdening the farmers [12]. [13] reported that 20% of farmers in Turkey experienced losses when implementing the introduced technology.…”
Section: Introductionmentioning
confidence: 99%